2003
DOI: 10.1002/ejoc.200300411
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Nucleophilic Substitution of (Chloroalkyl)oxazolines with Nitroarenes: Synthesis of (Nitrobenzyl)oxazolines

Abstract: 2‐Chloroalkyloxazolines 1a and 1b react with nitroarenes in the presence of tBuOK in DMSO to give, upon acidic quenching, substituted nitroaryloxazolines 2a, 2b, 3a, 9, 10, 11a−d, 12−19, and 21−22, probably by vicarious nucleophilic substitution (VNS). The reaction of 1a is poorly regioselective, while that of 1b is completely para regioselective, thus showing that the coupling is sterically controlled. Trapping of the carbanionic intermediate B of the VNS reaction with electrophiles furnished α,α‐disubstitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In a previous paper we reported that carbanions of (chloroalkyl)oxazolines couple efficiently with nitroarenes to furnish (nitrobenzyl)oxazolines according to a VNS process 7. In order to ascertain the generality of the VNS reaction of metallated (chloroalkyl)heterocycles, we embarked in a study focused on the reaction of carbanions of chloroalkyl derivatives of thiazole, benzothiazole and pyridine with nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous paper we reported that carbanions of (chloroalkyl)oxazolines couple efficiently with nitroarenes to furnish (nitrobenzyl)oxazolines according to a VNS process 7. In order to ascertain the generality of the VNS reaction of metallated (chloroalkyl)heterocycles, we embarked in a study focused on the reaction of carbanions of chloroalkyl derivatives of thiazole, benzothiazole and pyridine with nitroarenes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that carbanions of α-chloroalkyl-and dichloromethyl-oxazolines undergo the VNS reaction with a variety of nitroarenes, producing nitrobenzyloxazolines 12 and α-chloronitrobenzyl oxazolines. 13 The latter compounds can enter in situ the Darzens reaction with aldehydes giving nitroaryl oxazolinyl oxiranes.…”
mentioning
confidence: 99%